Numerical methods for post-formed timber gridshells: Simulation of the forming process and assessment of R-Funicularity. (1st March 2020) - Regalo, Maria Luisa; Gabriele, Stefano; Salerno, Ginevra; Varano, Valerio
Highlights: A nonlinear staged construction analysis is adopted to simulate the forming process. The orientation of the laths affects the active bending during the forming process. A graphic tool provides a synthetic reading of the structural behavior of gridshell. Abstract: A nonlinear staged construction analysis is adopted here to simulate the forming process of timber gridshell. In this respect, particular attention is paid to the modelling of the cylindrical joints connecting the orthogonal laths. Cylindrical joints enable the initially flat lattice to be formed into a doubly curved gridshell shape; therefore, accurate modelling of the joints' mechanical behaviour is a crucial aspect when simulating the forming process of timber gridshells. Another important parameter influencing the gridshell shape is the orientation of laths making up the initially flat lattice. Using an equivalent continuum definition, the final geometry of the gridshells, obtained from different laths orientations, is analysed in here to assess how laths orientation affects the structural shape in terms of funicularity. The Relaxed Funicularity Ellipse method presented in Gabriele et al. (2018) is used for such purpose.